Feasibility Study of Solar Power Generation System for Public Street Lighting - Muhammad Fadel Ibrahim; Imadudin Harjanto; Bambang Hadi Kunaryo (Universitas PGRI Semarang, 2022)
One of the uses of electricity that is widely used by society today is as a source of lighting. The increasing level of community mobility makes all activities require lighting. One part that is important and requires lighting is a highway or public road. PJU is a lighting lamp that is public (for the common good) and is usually installed on roads and certain places such as parks and other public places. PJU (street lighting) or road lighting is a light source that is installed as street lighting at night. Public street lighting using solar power is a cheap and economical alternative to be used as a source of lighting electricity because it uses a new and unlimited renewable energy source that comes from nature, namely solar energy. This study aims to determine the feasibility of solar street lighting in the future as a substitute for conventional public street lighting in the future by looking at the Net present cost, and Break even point assisted by HOMER software version 3.10.3. And the results obtained from the calculation of the Net present cost of conventional street lighting costs less, which is only Rp. 30,245,473 and the Net present cost of solar street lighting costs an initial investment of Rp. 128,341,312 and the BEP (Break even point) graph that has not been found to break even.